Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s41109-021-00373-8
|View full text |Cite
|
Sign up to set email alerts
|

Correlation networks of air particulate matter ($$\hbox {PM}_{2.5}$$): a comparative study

Abstract: Over the last decades, severe haze pollution constitutes a major source of far-reaching environmental and human health problems. The formation, accumulation and diffusion of pollution particles occurs under complex temporal scales and expands throughout a wide spatial coverage. Seeking to understand the transport patterns of haze pollutants in China, we review a proposed framework of time-evolving directed and weighted air quality correlation networks. In this work, we evaluate monitoring stations’ time-series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…The strength of a potential interaction relationship between PM pollution in two adjacent cities is measured using a statistical measure called time lag-adjusted Pearson correlation coefficient. The time lag-adjusted Pearson correlation coefficient is calculated using cross correlation method ( 25 27 ).…”
Section: The Framework For Characterizing the Multilateral And Direct...mentioning
confidence: 99%
“…The strength of a potential interaction relationship between PM pollution in two adjacent cities is measured using a statistical measure called time lag-adjusted Pearson correlation coefficient. The time lag-adjusted Pearson correlation coefficient is calculated using cross correlation method ( 25 27 ).…”
Section: The Framework For Characterizing the Multilateral And Direct...mentioning
confidence: 99%
“…Emerging evidence suggests potential links between exposure to polluted air and the epidemic of COVID-19(Chen et al 2021 ; Chen et al 2020 ; Konstantinoudis et al 2021 ). Research has shown that the airborne transmission is highly virulent (Srivastava 2021 ), particulate matter can be used as a carrier to carry viruses to spread it everywhere (Vlachogiannis et al 2021 ; Yao et al 2020 ), and respiratory infectious disease viruses that are efficiently transmitted through particulate matter can remain stable for a longer period of time.…”
Section: Introductionmentioning
confidence: 99%